1992
DOI: 10.1090/s0002-9939-1992-1137223-8
|View full text |Cite
|
Sign up to set email alerts
|

Convergent free sequences in compact spaces

Abstract: Abstract.We prove that if k is an uncountable regular cardinal and a compact T2 space X contains a free sequence of length k , then X also contains such a sequence that is convergent. This implies that under CH every nonfirst countable compact T2 space contains a convergent oi\-sequence and every compact T2 space with a small diagonal is metrizable, thus answering old questions raised by the first author and M. Husek, respectively. IntroductionWhile there are compact T2 spaces with no nontrivial convergent co-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 3 publications
0
20
0
1
Order By: Relevance
“…We will see in Theorem 2.8 that a similar application of elementary sequences will imply that a csD space will have a property stronger than countable tightness. This approach was inspired by the Juhász-Szentmiklóssy proof from [6] where it is shown that if a compact space does not have countable tightness, then it will contain a converging (free) ω 1 -sequence (also making essential use of Sapirovskiȋ's result). A csD space can not contain a (co-countably) converging ω 1sequence.…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…We will see in Theorem 2.8 that a similar application of elementary sequences will imply that a csD space will have a property stronger than countable tightness. This approach was inspired by the Juhász-Szentmiklóssy proof from [6] where it is shown that if a compact space does not have countable tightness, then it will contain a converging (free) ω 1 -sequence (also making essential use of Sapirovskiȋ's result). A csD space can not contain a (co-countably) converging ω 1sequence.…”
Section: 2mentioning
confidence: 99%
“…There are a number of very interesting results known for csD spaces and we recommend [4] as an excellent reference. In particular, it is known that csD spaces have countable tightness ( [6]) and that it follows from CH that csD spaces are metrizable ( [5,6]). One of our main results is that ccc subspaces of a csD space have countable π-weight.…”
Section: Introductionmentioning
confidence: 99%
“…Since H. Zhou had shown in [56] it to be consistent with ZFC that every compact Hausdorff space with a small diagonal is metrizable, Arkhangel'skii and Tkačhuk were able to obtain the relative consistency of the assertion that a compact Hausdorff space K is metrizable if C p (K ) is Shanin. I. Juhász and Z. Szentmiklóssy showed in [26] that every compact space with a small diagonal is metrizable under the Continuum Hypothesis (CH). It follows that, under CH, [7]; it is still an open problem (see [7, Problem 68]) whether this result holds without any additional set-theoretic assumptions.…”
Section: Chain Conditions For Banach Spacesmentioning
confidence: 99%
“…Juhász and Szentmiklóssy established in [12] that if the diagonal of a compact space X is small then X has countable tightness so CH is sufficient for metrizability of a compact space with a small diagonal. Since then, quite a few results were obtained about spaces with a small diagonal (see e.g., [9]).…”
Section: Theorem the Space C P (X) Is ω-Embedded In A σ -Compact Framentioning
confidence: 99%